Anti-inflammatory effects of nobiletin on TLR4/TRIF/IRF3 and TLR9/IRF7 signaling pathways in prostate cancer cells. (3rd March 2020) - Deveci Ozkan, Asuman; Kaleli, Suleyman; Onen, Hacer Ilke; Sarihan, Mehmet; Guney Eskiler, Gamze; Kalayci Yigin, Aysel; Akdogan, Mehmet
Abstract: Background: Toll-like receptors (TLRs) are often expressed in natural immune cells as well as in tumor cells. TLR4 exhibits both tumor promoting and tumor-suppressing roles and higher TLR9 expression is an important marker of poor prognosis in prostate cancer (PCa). Nobiletin (NOB) is an O-methylated flavonoid and NOB has been proven to have anti-cancer effect in PCa cells. However, there is no study in the literature investigating the potential anti-inflammatory effects of NOB on the TLR signaling pathways in cancer. Therefore, we aimed to explore the potential anti-inflammatory effects of NOB on the TLR4/TRIF/IRF3 and TLR9/IRF7 signaling pathways in different types of PCa cell lines, for the first time. Material and methods: In the current study, the cytotoxic effect of NOB PC-3 (hormone-independent and metastatic) and LNCaP cells (hormone-dependent) was evaluated by WST-1 assay. Furthermore, the inhibitory effects of NOB on TLR4/TRIF/IRF3 and TLR9/IRF7signaling pathway were determined by RT-PCR, western blotting and ELISA analysis. Results: NOB demonstrated an inhibitory effect on PCa cell growth and LNCaP cells were more sensitive to NOB than PC-3 cells due to androjen receptor status. Furthermore, NOB alone could suppress TLR4/TRIF/IRF3 and TLR9/IRF7 signaling pathways through the downregulation of their associated pathways (mRNA and related protein levels) and the release of IFN-α and IFN-β compared to LPS or CpG-ODN stimulated PCa cells. Conclusions: NOB potentially inhibited TLR4 and TL9-dependent signaling pathway in PCa cells. However, the efficacy of NOB was different in PCa cells due to the hormone status and aggressive features.